The importance of psychological contracts for safe work during pandemics - Petery, Gigi; Parker, Sharon; Zoszak, Leah (CAMBRIDGE UNIV PRESS, 2021)
COVID-19 has shone a spotlight on how the effects of a pandemic can reverberate throughout a broad spectrum of work-related processes, as eloquently described in the focal article (Rudolph et al., 2020). However, a critical topic overlooked by the authors is the explicit and implicit role organizations play in protecting the health of workers and the community at large. Accordingly, we propose psychological contracts, specifically in relation to workplace health and safety (Rousseau, 1989; Walker & Hutton, 2006), as an area warranting greater attention at this time from researchers and practitioners alike. Health and safety psychological contracts are crucial given the occupational hazards created by highly contagious diseases. According to recent pre-pandemic estimates, 10% of workers in the U.S. are exposed at work to disease or infection more than once per week, and 18.4% are exposed more than once per month (Barker et al., 2020). In fact, it is estimated that pandemic disease exposure may be greater at work than elsewhere, which has implications for disease transmission to workers and communities alike. For instance, 17 of the first 25 community transmitted cases of COVID-19 in Singapore are believed to be associated with workplace exposure (e.g., infected individual in contact with retail, hospitality, and transportation workers; Koh, 2020). Unlike other forms of workplace risk that do not involve contagions, infected workers can also increase community exposure to contagious diseases, particularly when transmission is airborne and occurs when individuals are asymptomatic, thereby constituting a greater scale of workplace risk than was seen pre-pandemic. Therefore, understanding how to protect the workforce is a critical issue that warrants serious attention. In what follows, we highlight the importance of psychological contracts for ensuring workplace safety in the context of the current pandemic. We then discuss three key issues for research and practice related to psychological contracts that might apply during a pandemic.